KEWAJIBAN NOTARIS DALAM MERAHASIAKAN ISI AKTA DIKAITKAN DENGAN PASAL 66 UNDANG - UNDANG NOMOR 2 TAHUN 2014 PERUBAHAN ATAS UNDANG - UNDANG NOMOR 30 TAHUN 2014 TENTANG JABATAN NOTARIS - KRISTINA SIAHAAN (PREMISE LAW JURNAL, 2017)
Notary is a public official who makes authentic deed. Notaries running his positition as a public official,an addition to abiding by the rules of office, also bounded by the oath of office which has taken at the time he appointed as a notary, such as keep the contents of the deed and the information obtained. This research is normative. The collection of data’s from the literature study were analyzed qualitatively describing as well as analyzing the existing problems, in this case used deductive-inductive method which will be drawn the appropriate conclusions. The results showed a Notary as a public official who makes authentic deed, must keep the contens of the deed it self and any information obtained in the office, caused by the Notary as a public official who has the privilege, namely the right of refusal, name the right not to give testimony. Legislation requires the provision and protection of the Notary function, in particular in terms to dublicate the minuta. In article 66 parargraf (1) of the Law of the Notary office of the honorary Council approval Notary is to give the application. If the Notary negligent or careless in performing their duties as a public official who makes authentic deeds, notary can been issued by the parties or clients were dissatisfied or feel disadvantage as a result of an authentic deed made by the Notary, Notaries in this case may be sued in civil and criminal, and accountability morally, ethically an legally to the public. Keywords: Liability, Notary, Keeping Content Act.